12t-8t=-52solvet

Simple and best practice solution for 12t-8t=-52solvet equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12t-8t=-52solvet equation:


Simplifying
12t + -8t = -52solvet

Combine like terms: 12t + -8t = 4t
4t = -52solvet

Solving
4t = -52elostv

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '52elostv' to each side of the equation.
52elostv + 4t = -52elostv + 52elostv

Combine like terms: -52elostv + 52elostv = 0
52elostv + 4t = 0

Factor out the Greatest Common Factor (GCF), '4t'.
4t(13elosv + 1) = 0

Ignore the factor 4.

Subproblem 1

Set the factor 't' equal to zero and attempt to solve: Simplifying t = 0 Solving t = 0 Move all terms containing t to the left, all other terms to the right. Simplifying t = 0

Subproblem 2

Set the factor '(13elosv + 1)' equal to zero and attempt to solve: Simplifying 13elosv + 1 = 0 Reorder the terms: 1 + 13elosv = 0 Solving 1 + 13elosv = 0 Move all terms containing t to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 13elosv = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 13elosv = 0 + -1 13elosv = 0 + -1 Combine like terms: 0 + -1 = -1 13elosv = -1 Add '-13elosv' to each side of the equation. 13elosv + -13elosv = -1 + -13elosv Combine like terms: 13elosv + -13elosv = 0 0 = -1 + -13elosv Simplifying 0 = -1 + -13elosv The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Solution

t = {0}

See similar equations:

| 85/4*9-17+56 | | 5n-5/3 | | .7p+4.6=7.3-.2 | | -11+6a=5+2a | | 2=-2(x)+b | | -294/-7 | | 3x-z=9 | | 2m+8-4m=27 | | 2x=y-4 | | -124-12x+6x=32 | | .5(12N+4)=14+10N | | 4.5x+4=7x-6 | | 3x/2-1=x/7 | | -3x-9x=-3 | | 8y=-6x+24 | | -9y+2x=11 | | T+97=513 | | y^2+1y= | | 3y^2+7y^2+2y^3= | | 7(-21)-3y=-21 | | -4b-5+2d=10 | | 21=6-x-4 | | 2.5y+0z=-2.5 | | 7(7p+1)-4p=13(3p-2) | | y=5(2x-9) | | 1/7-51/2=9/14 | | 72500+10.50x=2500 | | .25(60+16s)=0.3333333333333333(45+12s) | | a^2-15=0 | | 5y-2y+9y=-16 | | 18=5x-3x | | 7-3n=-4n+1 |

Equations solver categories